Bevacizumab Added to Neoadjuvant Chemotherapy for Breast Cancer - Harry D. Bear; Gong Tang; Priya Rastogi; Charles E. Geyer; André Robidoux; James N. Atkins; Luis Báez-Díaz; Adam Brufsky; Rita S. Mehta; Louis Fehrenbacher; James A. Young; Francis M. Senecal; et al. (2012)
Bevacizumab and the antimetabolites capecitabine and gemcitabine have been shown to improve outcomes when added to taxanes in patients with metastatic breast cancer. The primary aims of this trial were to determine whether the addition of capecitabine or gemcitabine to neoadjuvant chemotherapy with docetaxel, followed by doxorubicin plus cyclophosphamide, would increase the rates of pathological complete response in the breast in women with operable, human epidermal growth factor receptor 2 (HER2)–negative breast cancer and whether adding bevacizumab to these chemotherapy regimens would increase the rates of pathological complete response.